Association between Serum Uric Acid Levels and Perinatal Outcome in Women with Preeclampsia - Robinson Uchenna Ugwuanyi; Irozuruike Munachiso Chiege; Felix Eke Agwu; George Uchenna Eleje; Nonso Martin Ifediorah (Obstetrics and Gynecology International)
Objectives. To compare serum uric acid levels with disease severity and perinatal outcome among preeclamptic and normal pregnant women. Materials and Methods. This was a case-control study carried out in Federal Medical Centre, Umuahia, Nigeria. Consenting pregnant women were consecutively recruited into two groups comprising pregnant women diagnosed with preeclampsia and normotensive nonproteinuric pregnant women. Exclusion criteria included pregnant women who were current smokers, took alcohol, and diagnosed with multiple gestation, diabetes mellitus, or renal failure. Associations between categorical variables such as preeclampsia severity and perinatal outcomes were done using logistic regression while means of continuous variables such as serum uric acid were compared using Student’s t-test. Data were presented using odds ratios (ORs) with 95% confidence intervals (95% CI) and a statistical significance level set at P value ˂ 0.05. Data analysis was done using Statistical Package for Social Sciences version 22. Results. One hundred and two participants were finally analysed. Fifty-one participants were recruited in each arm. Women with preeclampsia had significantly high serum uric acid level versus controls (6.08 ± 0.49 mg/dL vs. 5.20 ± 0.19; P<0.001). Women with elevated serum uric acid levels (˃6 mg/dL) were found to be 4 times more likely to have severe preeclampsia (P=0.022, OR = 4.00, 95% CI = 1.225–13.056), 66 times more likely to have APGAR score ˂7 in the first minute (P<0.001, OR = 66.00, 95% CI = 6.991–623.128), and 3 times more likely to have lower birth weight (P=0.038, OR = 3.400, 95% CI = 1.073–10.775) than those with normal serum uric acid levels. Conclusions. The mean serum uric acid level in a preeclamptic is higher than that of normal pregnant control, and higher levels are associated with severity of the disease and significantly associated with poorer perinatal outcome.